2017
DOI: 10.1016/j.jid.2017.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of CXCL12 in Serum of Patients with Vitiligo

Abstract: et al. Protective effects of platinum nanoparticles against UV-lightinduced epidermal inflammation. Exp Dermatol 2010;19:1000e6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…In the skin, dysregulation of SDF1 signalling was previously linked to autoimmune and chronic inflammatory dermatological disorders, such as psoriasis, atopic dermatitis and lupus 19 . Studies of vitiligo performed in animal models have shown that melanocyte-derived SDF1 plays an important role in the activation of melanocyte-specific autoimmunity and results in continuous loss of melanocytes 39 . The results of the present study suggest that beyond the case of vitiligo, in which an immune response is thought to be responsible for the destruction of normal melanocytes, SDF1 plays an inhibitory role in controlling cutaneous pigmentation in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…In the skin, dysregulation of SDF1 signalling was previously linked to autoimmune and chronic inflammatory dermatological disorders, such as psoriasis, atopic dermatitis and lupus 19 . Studies of vitiligo performed in animal models have shown that melanocyte-derived SDF1 plays an important role in the activation of melanocyte-specific autoimmunity and results in continuous loss of melanocytes 39 . The results of the present study suggest that beyond the case of vitiligo, in which an immune response is thought to be responsible for the destruction of normal melanocytes, SDF1 plays an inhibitory role in controlling cutaneous pigmentation in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…88,89 Biomarkers of disease activity can help identify subjects with active inflammation and might serve as excellent early indicators of treatment responses. 12,14,[90][91][92][93] These include both serum biomarkers and biomarkers that can be directly measured within lesional skin, which might have better sensitivity and specificity. Recently, we described a minimally invasive skin-sampling technique through induction of blisters in lesional and nonlesional skin, which provides blister fluid for analysis of infiltrating immune cells and inflammatory cytokines that reflect both disease activity, as well as early treatment responses.…”
Section: Planning For Efficient and Informative Clinical Trialsmentioning
confidence: 99%
“…The capacity of each individual region for assessing disease activity was evaluated using receiver operating characteristic curve analysis and revealed diagnostic capacities comparable to results previously reported for blood markers in the field such as CXCL9, CXCL10, sCD25, sCD27 and CXCL12. [ 1,14‐16 ] Area under the curves of 0.78 for the intensity at 1139 nm (Figure 2F), 0.73 for the intensity at 1344 nm, 0.71 for the intensity at 1646 nm, 0.69 for the intensity at 1839 nm and finally 0.70 for the intensity at 1884 nm was found. The most discriminating region around 1139 nm can be associated with C‐H and C = O carbonyl groups, and a change in intensity has previously been reported during oxidation.…”
Section: Resultsmentioning
confidence: 99%